Prediction Model of Bailing Oil Dynamic Production and Periodic Optimization. Issue 1 (1st February 2023) - Zhu, Jing; Zhang, Fuxing; He, Jinbao; Tang, Li
Abstract: As a production method of low production wells and remote oil wells, bailing oil recovery is particularly important for its reasonable working system. The dimensionless bottom hole flowing pressure is solved by establishing the seepage mechanics equation of infinite homogeneous formation, and the productivity of bailed well is predicted by using the direct relationship between bottom hole flowing pressure and unit flow rate. On this basis, a mathematical model of the net income of bailing wells is established to determine a reasonable bailing period with economic benefits as the goal, and solve the problem that the oil bailing system relies on experience and lacks theoretical guidance.